ZigBee wireless networks and transceivers. - Farahani, Shahin, ....- (Amsterdam : Elsevier, 2008)
Table of Contents Chapter 1: ZigBeeTM Basics Chapter 2: ZigBeeTM / IEEE 802.15.4 Networking Examples Chapter 3: ZigBeeTM / IEEE 802.15.4 Protocol Layers Chapter 4: Transceiver Requirements Chapter 5: RF Propagation, Antennas, and Regulatory Requirements Chapter 6: Battery Life Analysis Chapter 7: Location Estimating Using ZigBeeTM Chapter 8: ZigBeeTM Coexistence Chapter 9: Related Technologies